Fusão e aquisição para obtenção de vantagem competitiva: um estudo em supermercados - Ortolan, Victor Zompero (2019)
This study seeks to understand the merger and acquisition strategy as a source of competitive advantage for small and medium-sized companies in supermarkets located in interior regions of the State of São Paulo. In order to better understand the phenomena to be studied, two companies in the supermarket segment operating in the western region of the State of São Paulo were researched and using or already used such a strategy. Therefore, we sought to know through a qualitative exploratory research carried out with the six executives responsible for the management of the companies. This study aims to analyze if the merger and acquisition process generates Competitive Advantage for the company and if it is Sustainable. Data collection was performed and treated through content analysis. The referred study resulted in the identification of strategic actions carried out by companies in search of a strategic positioning differentiated in the market in which they are inserted. The present study presents in its final considerations the use of the Fusion and Acquisition Strategy by the companies focus as a factor of important development of a Sustainable Competitive Advantage.